2020
DOI: 10.1021/acs.inorgchem.0c01084
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic versus Electrophilic Activation of Hydrogen Peroxide over Zr-Based Metal–Organic Frameworks

Abstract: Zr-based metal–organic frameworks (Zr-MOF) UiO-66 and UiO-67 catalyze thioether oxidation in nonprotic solvents with unprecedentedly high selectivity toward corresponding sulfones (96–99% at ca. 50% sulfide conversion with only 1 equiv of H2O2). The reaction mechanism has been investigated using test substrates, kinetic, adsorption, isotopic (18O) labeling, and spectroscopic tools. The following facts point out a nucleophilic character of the peroxo species responsible for the superior formation of sulfones: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 119 publications
10
58
0
Order By: Relevance
“…The unprecedentedly high selectivity toward sulfones observed at low conversions of thioethers implies that nucleophilic oxidizing species predominate over electrophilic ones in Zr‐MOFs. The capability of UiO‐66 and UiO‐67 to epoxidize electron‐deficient C=C bonds in α,β‐unsaturated compounds also supported this conclusion [7b] …”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…The unprecedentedly high selectivity toward sulfones observed at low conversions of thioethers implies that nucleophilic oxidizing species predominate over electrophilic ones in Zr‐MOFs. The capability of UiO‐66 and UiO‐67 to epoxidize electron‐deficient C=C bonds in α,β‐unsaturated compounds also supported this conclusion [7b] …”
Section: Introductionmentioning
confidence: 57%
“…Finally, we tried to analyze a possible role of defects in the Zr‐MOF structures in the H 2 O 2 ‐based catalytic oxidations. Previously, two groups concluded that defects play a significant role in the thioether oxidation over UiO‐66 [6c, 7b] . TGA measurements showed that the concentration of defects corresponding to the total amount of terminal Zr(OH/H 2 O) groups decreased in the order Zr‐abtc > MIP‐200 > UiO‐67 > UiO‐66 (Table S2, Figures S8–S12 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations